Investigation of a low‐power, double‐sided switched reluctance generator for wave energy conversion. Issue 2 (1st March 2013) - Pan, Jianfei; Zou, Yu; Cao, Guangzhong
Abstract : In this paper, a low‐power, direct‐drive, double‐sided linear switched reluctance generator (LSRG) is designed and constructed as one of the components of generator matrix for wave power utilizations by direct energy conversion. This machine has the characteristics of simple construction, mechanical robustness, and maintenance free. Following the theoretical background of linear power generation, characteristic investigation is performed by finite element analysis, which shows that each phase can be controlled individually and normal forces can be approximately counteracted from the double‐sided structure. Both preliminary power simulation and experimental results show that there is an optimized generation region for turn‐on and turn‐off position control strategy. The closed loop test based on Pulse Width Modulation (PWM) of current waveforms also demonstrate that for a wide range of wave speed excitations, PWM scheme should be combined with other control strategies for uniform current level regulations.